Pragmatic Features of the Word Order in Speech - Sobirov Anvar Kuvandikovich (Researchparks Publishing, 2022)
Language is the main tool that ensures the emergence of human thoughts. Therefore, the concept of speech activity is realized in close connection with pragmatics, which denotes the Greek meanings